TINGKAT EFISIENSI PELAYANAN EKSPEDISI DI KOTA LHOKSEUMAWE MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS: THE EFFICIENCY LEVEL OF EXPEDITION SERVICES IN LHOKSEUMAWE CITY USING THE DATA ENVELOPMENT ANALYSIS (DEA) METHOD - Silvia Nanda; Dahlan Abdullah; Zara Yunizar (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
Lhokseumawe is one of the economic centers in Aceh that has a role in supporting distribution and services. With the development of e-commerce and the trading industry, the need for expedition services is increasing. Improved efficiency in the expedition service section is one way that can be done by the company to always meet customer satisfaction. The study implemented the CCR model Data Envelopment Analysis (DEA) method that aims to measure the efficiency of expedition services. There are four samples of companies: Shopee Express, J&T, JNT, and TIKI. The input variables used include the number of employees, number of vehicles, and operational costs, while the output variables include the number of delivered packages, the number of customers, and the number of timely delivery. The results showed that Shopee Express, J&T and JNE have an efficiency value of 1, which indicates that all three expeditions have utilized the input optimally to produce output. Meanwhile, TIKI has an efficiency value of 0.057, which indicates that it is still far from efficient conditions that require further evaluation to optimize input and output like all three other expeditions. This research not only contributes academically but also recommendations for expedition companies, so it can be the basis for strategic decision making to improve the competitiveness and quality of logistics services at Lhokseumawe.